3rd France-Russia Seminar 2007
DOI: 10.1051/names2007004
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Hard Nanostructured Coatings in Cr-B-N System

Abstract: The CrB 2 thin coatings are of interest because of their high hardness, wear-and corrosion resistance [1,2]. Incorporation of nitrogen in transition metal-boron systems (TiB 2 , ZrB 2 etc.) often leads to enhancing of chemical, mechanical and tribological characteristics [3,4]. The objective of the present study is the investigation of structure and properties of Cr-B-N coatings.The CrB 2 targets were synthesized from exothermal powder mixtures by means of selfpropagating high-temperature synthesis [5]. The Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The first layer (L1) was characterized by the presence of Al and O (as detected by EDS). This suggested that Al 2 O 3 crystallites formed as a consequence of the outward Al diffusion to the free surface [75,76]. Preferential oxidation of Al with respect to Ti at high temperature was reported by A. Joshi et al in [81].…”
Section: Ti-cr-b-n and Ti-al-si-b-n Coatingsmentioning
confidence: 67%
See 1 more Smart Citation
“…The first layer (L1) was characterized by the presence of Al and O (as detected by EDS). This suggested that Al 2 O 3 crystallites formed as a consequence of the outward Al diffusion to the free surface [75,76]. Preferential oxidation of Al with respect to Ti at high temperature was reported by A. Joshi et al in [81].…”
Section: Ti-cr-b-n and Ti-al-si-b-n Coatingsmentioning
confidence: 67%
“…Finally, coarse grains with an average size of 500 nm constitute the layer directly in contact to the substrate (L5). EDS indicates a large content of Cr and some Ti, N and B [73][74][75].…”
Section: Ti-cr-b-n and Ti-al-si-b-n Coatingsmentioning
confidence: 99%
“…The SHS targets passed successful tests in various types of installations, namely, dc magnetron systems (MS) [1, 9, 12-14, 15-17, 18-24], high-frequency [25] and pulsed MS [11], MS with additional inductively coupled plasma [26], and arc evaporators [27]. Over the last several years, using the magnetron sputtering of SHS targets, hard coatings were obtained in the systems Ti-Si-N [9,12,28], Ti-B-N [10,13,29,30], Ti-Si-B-N [4,13,29], Ti-Si-C-N [13,29], Ti-Al-C-N [13,29], Ti-C-N [31], Ti-Mo-C-N [31], Ti-Al-B-N [32], Ti-Al-Si-B-N [17,18,30], Ti-Cr-B-N [10,12,14,17,30], Cr-B-N [10,12,33,34], Ti-Zr-C-O-N [19], Ti-Ta-Ca-P-C-O-N [23,24], Ti-Cr-Al-C-N [35,36], etc. Taking into account the increase in demand for various compositions of composite targets, we decided that it is important to present the data on the features of the synthesis of the most interesting and necessary classes of SHS targets differing in regards to their combustion mechanisms and structure formation in the form of the review.…”
Section: Introductionmentioning
confidence: 99%